2016
DOI: 10.1093/ofid/ofw249
|View full text |Cite
|
Sign up to set email alerts
|

Using Procalcitonin to Guide Antibiotic Therapy

Abstract: Procalcitonin levels rise in response to systemic inflammation, especially of bacterial origin. Multiple randomized controlled trials have demonstrated that procalcitonin-based algorithms can safely reduce antibiotic use in 2 clinical scenarios. First, in stable, low-risk patients with respiratory infections, procalcitonin levels of <0.25 µg/L can guide the decision to withhold antibiotics or stop therapy early. Second, in critically ill patients with suspected sepsis, clinicians should not initially withhold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 52 publications
1
77
0
4
Order By: Relevance
“…Multiple randomized controlled trials have demonstrated that PCT levels of <0.25 mg/L can guide the decision to withhold antibiotics or stop therapy early. 19,20 Since the approval of FilmArray respiratory panel tests, only a few studies have evaluated the clinical impact after implementation of the multiplex PCR respiratory panel on patients with less severe acute reparatory illness. 8,13e15 To date, no study has focused on older adults with severe acute respiratory illness.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple randomized controlled trials have demonstrated that PCT levels of <0.25 mg/L can guide the decision to withhold antibiotics or stop therapy early. 19,20 Since the approval of FilmArray respiratory panel tests, only a few studies have evaluated the clinical impact after implementation of the multiplex PCR respiratory panel on patients with less severe acute reparatory illness. 8,13e15 To date, no study has focused on older adults with severe acute respiratory illness.…”
Section: Introductionmentioning
confidence: 99%
“…The use of combination therapies is recommended for patients who develop severe sepsis/septic shock due to these MDR pathogens and for immunocompromised or febrile neutropenic septic patients and septic patients hospitalized in ICUs. Randomized clinical trials investigating the efficacy of combination therapies currently in use are needed [94,99] .…”
Section: Rarely Resort To the Use Of Combined Antibiotic Therapiesmentioning
confidence: 99%
“…This practice could influence negative blood culture results which were initially considered as gold standard and thus reference point for the analysis of the performance of the biomarkers. In addition, it may not be possible to anticipate the influence the antibiotics might have on the expression and half-life of specific biomarkers in blood [16,20].…”
Section: Performance Of Biomarkers In the Prediction Of Bloodstream Bmentioning
confidence: 99%
“…Currently, many authorities recommends use of PCT as clinical guide for diagnosis of sepsis in emergency situations prior to administration of antibiotic therapy [15]. Moreover, serum levels of PCT correlates well with the degree of infectious load and can safely be used as a guide for dose deescalating or discontinuation of antibiotic use [16]. In order to improve predictive value of markers for bloodstream bacterial infections, one approach is the combination of prediction rules of different tests for clinical and laboratory markers [17].…”
mentioning
confidence: 99%